Interpersonal Communication and Problem Solving in Improving the Performance of Foster Parents of Students in Islamic Boarding Schools - Hamzah, M Fakhroni; Mansur, Umar; Agus R, Abu Hasan; Mundiri, Akmal; Thohir, Putri Fahmadia Dinda Maulida (Al-Qalam Institue, 2024)
This study aims to identify and analyze the role of interpersonal communication and problem-solving strategies in improving the performance of foster parents in Islamic boarding schools. The main problem raised is the lack of effectiveness of foster parents due to communication barriers and internal conflict resolution. This study uses a qualitative approach with a case study method at the Nurul Jadid Islamic Boarding School in the Ar Rumi area. Data were collected through in-depth interviews and participatory observations of kyai, foster parents, and students. The results of the study indicate that the pattern of interpersonal communication between kyai and foster parents takes place in the form of routine and structured two-way interactions, with kyai as the provider of direction and foster parents as the reporter. Problem solving strategies through mediation and counseling have proven effective in creating a harmonious foster atmosphere. In conclusion, good interpersonal communication and the right problem solving approach significantly improve the readiness and performance of foster parents in fostering students. This study contributes to strengthening the foster management system in the Islamic boarding school environment.